Pengaruh Puzzle Angka terhadap Kemampuan Pengenalan Simbol Bilangan pada Anak Usia Dini TK Kihajar Dewantoro VI - Salsabila R. Solang; Mita Sari; Elvian Bakari; Nabila Nabila; Nur Jelita Lauli; Zahwa Fitria Yusuf; Winda Lalu (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This study aims to determine the effect of using number puzzle media on the ability to recognize number symbols in early childhood at Kihajar Dewantoro VI Kindergarten. The background of this study is based on the importance of concrete and interesting media in supporting early mathematics learning, especially the introduction of number symbols in children aged 4–5 years. The study used a quantitative method with a quasi-experimental design through a comparison between conventional learning and learning using number puzzle media. Data were collected through observations of aspects of the ability to recognize number symbols and match numbers. The results showed that the average ability of children in conventional learning only reached a score of 6, while learning using number puzzle media increased significantly to a score of 13.1. These findings indicate that number puzzles can make children more focused, enthusiastic, and easier to understand number symbols in a concrete and meaningful way. Thus, number puzzle media is proven to be effective in improving the ability to recognize number symbols in early childhood and can be used as an alternative mathematics learning media in PAUD.